Improving Leadership Capacity of Local Leaders through Effective Communication and Conflict Management Training - Azhari, Azlan; Iswardhani, Indri; Macenning, A. Reski Almaida Dg; Nasir, Sri Astuti; Ridha, Achmad (Celebes Journal of Community Services, 2024)
This study examines the role of effective communication and conflict management training in enhancing the leadership capacity of local leaders, particularly in diverse and resource-constrained governance settings. It addresses the gap between theoretical frameworks, such as transformational and servant leadership, and their practical application in real-world contexts. A qualitative approach was employed using a systematic literature review methodology to synthesize insights from recent studies published between 2018 and 2024. The research focused on identifying best practices for integrating communication strategies and conflict resolution skills into leadership training programs. A thematic analysis of selected literature was conducted to ensure a comprehensive understanding of the core challenges and opportunities in local governance leadership. The study reveals that while transformational and servant leadership theories offer robust conceptual foundations, their practical implementation requires contextual adaptation. Effective communication strategies and conflict management techniques emerged as essential for fostering trust, collaboration, and transparency among stakeholders. Digital tools further enhance these processes, provided leaders understand the cultural and operational dynamics of their environments. Tailored training programs incorporating cultural sensitivity, real-world scenarios, and critical thinking exercises significantly improve leadership outcomes by addressing unique community challenges. This research contributes to both academic literature and practical applications by providing actionable insights for policymakers, organizations, and donor agencies. It highlights the need for context-specific leadership development programs that empower local leaders to navigate complexities effectively. These findings support the design of sustainable training initiatives that foster improved governance, stakeholder alignment, and long-term community outcomes.